NATURE-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING IN FORMING STUDENT CHARACTER AT SCHOOL - Burhanuddin, Hamam; Ariska, Ariska (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Nature-based learning is a model of learning that uses nature, preserves nature, and is based on the principles of learning about nature by using the media that exists around the natural environment. Through the concept of learning with nature students can learn while playing making learning interesting, fun, and not boring. Thus, students feel comfortable and happy to study in school for a long time. In general, the objective of this study is to describe the concept and implementation of Islamic Religion Education based on nature in student character formation at MI Plus Daarul Munjiyat Bektiharjo and SD Alam ElYamien Tuban, with a focus on: How the concept of learning Islamic religion education based on Nature in character formation in MI plus Daarul Münjiyat and SD Nature El- Yamien Tuba, and How the implementing of learning in Islamic religious education based upon nature in the student character forming at MIPlus Daarul munjiyat bektiharyo and SD Natural El-JamienTuba. The research uses a qualitative descriptive approach, namely data collection techniques through observations, interviews, and documentation. The analytical techniques used are data reduction, data presentation, and conclusion drawings. The validity of the findings was tested through prolonged participation, persistence, triangulation, and peer checking. The results of this research in the concept of learning Islamic religion education based on nature in character formation makes learning more interesting, enjoyable, and not boring. Because the concept of learning plays a role in learning by integrating four concepts: morality, science, leadership, and business